2021
DOI: 10.1007/s00268-020-05921-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance Score for Female and Male Residents in General Surgery Doing Supervised Real‐Life Laparoscopic Appendectomy: Is There a Norse Shield‐Maiden Effect?

Abstract: Background Gender bias may represent a threat to resident assessment during surgical training, and there have been concerns that women might be disadvantaged. There is a lack of studies investigating gender differences in ‘entry-level’ real-life procedures, such as laparoscopic appendectomy. We aimed to explore potential gender disparities in self-evaluation and faculty evaluation of a basic surgical procedure performed by junior surgical residents in general surgery. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Female residents’ tended to underestimate their abilities compared with faculty assessment has been the main topic in 3 papers,70,72,73 with male residents’ self-assessment scores demonstrating a stronger correlation with the attending score 72. On the contrary, in a study conducted in Norway71 assessing residents during laparoscopic appendicectomy, no negative gender bias toward women trainees was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Female residents’ tended to underestimate their abilities compared with faculty assessment has been the main topic in 3 papers,70,72,73 with male residents’ self-assessment scores demonstrating a stronger correlation with the attending score 72. On the contrary, in a study conducted in Norway71 assessing residents during laparoscopic appendicectomy, no negative gender bias toward women trainees was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…In a structured training programme described previously 16 , and in which both trainee and trainer have specific obligations and preparations to consider for enhanced learning during laparoscopic appendicectomy, we have previously shown that there was no difference between male or female trainees’ performance during surgical training 9 . A previous study also demonstrated that most trainees became proficient in laparoscopic appendicectomy when having completed around 30 procedures 10 ; however, the same investigation also found that the mastery of each of the procedure steps varied considerably, which led to the current in-depth analyses of the connectivity between each of the steps.…”
Section: Discussionmentioning
confidence: 90%
“…To further explore the weight of each step to the final procedure evaluation, an artificial neural network model was created using a multilayer perceptron. As we have previously demonstrated equal outcomes between trainee sex and described the association of absolute number on performance metrics 9 , we performed the analyses across the eight steps without covariates to specifically investigate the procedure steps influence on overall evaluation of the junior residents. To control for experience, a sensitivity analysis was performed for 20 or fewer, 30 or fewer, or more than 30 laparoscopic appendectomies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 A recent study performed at a surgical training program in Norway found that female surgical trainees received higher performance scores during real-time laparoscopic appendectomy than their male counterparts. 42 As more women enter specialties across all of medicine, growing evidence affirms that training and experience predict competence in medicine and surgery, not gender.…”
Section: Sexual Harassmentmentioning
confidence: 99%